Understanding the types of knowledge demonstrated by social work students while developing ePortfolios : case of UWC - Mungai, Paul (School of Education, 2015)
This study seeks firstly to understand the types of ePortfolios that the learners are expected to develop as per the rubric, secondly to understand the various types of knowledge that learners demonstrate during the process of creating ePortfolios, thirdly to determine the ePortfolio activity systems of second year learners and fourthly to determine the effectiveness of the rubric in assessing the various types of knowledge demonstrated by the learners while creating their ePortfolio.